2012
DOI: 10.1007/s12665-012-1603-5
|View full text |Cite
|
Sign up to set email alerts
|

Global change and long-term gully sediment production dynamics in Basilicata, southern Italy

Abstract: The Fossa Bradanica in Basilicata (S Italy) is\ud affected by almost 15% permanent Pleistocene and Holocene\ud gullies. In the past decades climate versus land use\ud management have dramatically increase both the soil loss\ud rate and the muddy-flooding frequency. In this paper the\ud impact of global change on soil production rates and erosion/\ud deposition dynamics at medium-time scale (1949–2000) for\ud two permanent gullies (Fosso Lavandaio and Fosso San\ud Teodoro) has been studied. Pluviometric regime,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Either very intense precipitation is associated with erosion (Archibold et al, 2003;Porto et al, 2014;Schnabel and Amelia, 1993;Sirvent et al, 1997;Valentin et al, 2005), or the cumulative effect of long duration low intensity events is more significant (Trustrum et al, 1999). Previous studies in different soil and climatic regimes identified event-based to weekly precipitation in the rainy season as primary drivers for soil erosion (Martınez-Casasnovas et al, 2002;Piccarreta et al, 2012;Poesen and Hooke, 1997;Renschler et al, 1999). In contrast, our research found that for Ultisols in a humid climate, a combination of antecedent precipitation and weekly total precipitation accumulation together can explain about 50% of variability in the erosion data.…”
Section: Temporal Resolutioncontrasting
confidence: 85%
“…Either very intense precipitation is associated with erosion (Archibold et al, 2003;Porto et al, 2014;Schnabel and Amelia, 1993;Sirvent et al, 1997;Valentin et al, 2005), or the cumulative effect of long duration low intensity events is more significant (Trustrum et al, 1999). Previous studies in different soil and climatic regimes identified event-based to weekly precipitation in the rainy season as primary drivers for soil erosion (Martınez-Casasnovas et al, 2002;Piccarreta et al, 2012;Poesen and Hooke, 1997;Renschler et al, 1999). In contrast, our research found that for Ultisols in a humid climate, a combination of antecedent precipitation and weekly total precipitation accumulation together can explain about 50% of variability in the erosion data.…”
Section: Temporal Resolutioncontrasting
confidence: 85%
“…Volumetric analysis have been performed also in Basilicata (Piccarreta et al 2012), where during the last century agricultural soils underwent continuous degradation, due to the highly erodible nature of outcropping terrains and to the anthropic pressure. An attempt to quantify the contribution of gully erosion to overall soil loss and sediment production, by adopting a consolidate procedure in GIS to determine medium-term sediment production and deposition rates in a large gully of Fossa Bradanica, was based on the subtraction of multi-date elevation values from DEMs, including sediment produced by different processes.…”
Section: Medium and Long-term Contribution Of Erosion In Morphodynamimentioning
confidence: 99%
“…Of the few examples reported in the literature, the best documented is the case of the Italian calanchi and biancane badlands that have been flattened to varying degrees for cereal cultivation stimulated by agrarian reforms of the 1950s and the European Union Common Agricultural Policy (Phillips, 1998;Clarke and Rendell, 2000;Piccarreta et al, 2006;Capolongo et al, 2008;Piccarreta et al, 2012). Of the few examples reported in the literature, the best documented is the case of the Italian calanchi and biancane badlands that have been flattened to varying degrees for cereal cultivation stimulated by agrarian reforms of the 1950s and the European Union Common Agricultural Policy (Phillips, 1998;Clarke and Rendell, 2000;Piccarreta et al, 2006;Capolongo et al, 2008;Piccarreta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%